2002
DOI: 10.1037/1524-9220.3.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Psychological predictors of sexual harassment: Authoritarianism, hostile sexism, and rape myths.

Abstract: Sexual harassment has been found to be common in the workplace. Forty-two percent to 88% of working women report having been sexually harassed. Recent research on sexual harassment has taken a cognitive approach, arguing that male sexual harassment of women results from 2 types of sexism in combination with stereotypes: hostile sexism and benevolent sexism. This study considers a model that a deeper personality characteristic, authoritarianism, contributes to the likelihood of sexual harassment, in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
129
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 15 publications
11
129
1
2
Order By: Relevance
“…Carroll (2009) found that moral disengagement (as measured by the MDS) in male college fraternity members was negatively correlated with moral judgment and positively associated with rape supportive attitudes, including greater attribution of blame to a female victim of ambiguous acquaintance rape. Given consensus among many researchers that sexually harassing behavior lies along a continuum of sexual aggression (e.g., Begany & Milburn, 2002;Kelly, 1988;Lonsway et al, 2008;Pina et al, 2009;Quina, 1990), it is feasible to expect this correlational pattern to replicate when moral disengagement (measured by the MDiSH) is tested in the context of an ambiguous case of hostile work environment harassment. Thus, in Study 3, we predicted that the MDiSH would display a negative correlation with moral judgment (operationalized as the perceived moral Moral Disengagement in Sexual Harassment 14 acceptability of hostile work environment harassment) and a positive correlation with attribution of blame to the female complainant.…”
Section: Assessing Convergent and Discriminant Validity Of The Mdishmentioning
confidence: 99%
“…Carroll (2009) found that moral disengagement (as measured by the MDS) in male college fraternity members was negatively correlated with moral judgment and positively associated with rape supportive attitudes, including greater attribution of blame to a female victim of ambiguous acquaintance rape. Given consensus among many researchers that sexually harassing behavior lies along a continuum of sexual aggression (e.g., Begany & Milburn, 2002;Kelly, 1988;Lonsway et al, 2008;Pina et al, 2009;Quina, 1990), it is feasible to expect this correlational pattern to replicate when moral disengagement (measured by the MDiSH) is tested in the context of an ambiguous case of hostile work environment harassment. Thus, in Study 3, we predicted that the MDiSH would display a negative correlation with moral judgment (operationalized as the perceived moral Moral Disengagement in Sexual Harassment 14 acceptability of hostile work environment harassment) and a positive correlation with attribution of blame to the female complainant.…”
Section: Assessing Convergent and Discriminant Validity Of The Mdishmentioning
confidence: 99%
“…Por ejemplo Begany y Milburn (2002) señalan la relación existente entre el sexismo hostil y actitudes autoritarias como predictoras de acoso sexual. Chapleau, Oswald y Sexismo y agresiones físicas, sexuales y verbales-emocionales en relaciones de noviazgo de estudiantes universitarios Electronic Journal of Research in Educational Psychology, 9(2), 541-564.…”
Section: Introductionunclassified
“…Ambivalent sexism is related to perpetration of sexual victimization; however, most of this relationship seems to be carried by hostile sexism (Abbey, McAuslan, Zawacki, Clinton, & Buck, 2001;Begany & Milburn, 2002;Caron & Carter, 1997;Forbes, Adams-Curtis, & White, 2004;Murnen, Wright, & Kaluzny, 2002). For example; both benevolent and hostile sexism were related to sexual harassment in a study of undergraduate men's and women's attitudes toward sexual harassment (Russell & Trigg, 2004); however, the correlation between hostile sexism and tolerance for sexual harassment was much higher than for benevolent sexism and tolerance.…”
Section: Gender Roles and Relationshipsmentioning
confidence: 99%